Anti diabetic property of aqueous extract of Stevia rebaudiana Bertoni leaves in Streptozotocin-induced diabetes in albino rats - Uswa Ahmad; Rabia Shabir Ahmad (BMC, 2018)
Abstract Background Stevia (Stevia rebaudiana) natural, non-caloric sugar substitute is rich source of pharmacologically important glycoside stevioside that is linked to the pathology and complications of diabetes. Methods The current research was carried out to explore the anti-diabetic effect of aqueous extract of Stevia rebaudiana leaves in albino rats. For this purpose, diabetes was induced by administration of streptozotocin (40 mg/kg body weight, intraperitoneally). The diabetic rats were administered with aqueous stevia extract at different dose levels (200, 300, 400 and 500 ppm/kg b.w) for 8 weeks; the control rats were fed basal diet during this period. Results Stevia aqueous extract improved caloric management and weight control by decreasing the feed intake and body weight gain. Furthermore, intake of stevia extract resulted in significant (P < 0.05) decrease in the random blood glucose level (− 73.24%) and fasting blood glucose (− 66.09%) and glycosylated (HbA1c) hemoglobin (5.32%) while insulin (17.82 μIU/mL) and liver glycogen (45.02 mg/g) levels significantly improved in the diabetic rats, compared with the diabetic and non-diabetic control rats after 8 weeks study period. Conclusions It is concluded that aqueous extact of stevia has anti-diabetic effects in albino rats, and therefore could be promising nutraceutical therapy for the management of diabetes and its associated complications.